The Production of Conversational Humor by Flouting Gricean Maxims in The IT Crowd Sitcom - Ilsa Krisdwiyani; Sharifah Hanidar (Universitas Gadjah Mada, 2022)
This study focuses on the Gricean maxim floutings found in the production of verbal humor by the characters in the show The IT Crowd, seasons one and two. This research aims to identify and classify the flouting of maxims, explain the rhetorical strategies employed, and the functions behind each flouting of the humorous utterances in the sitcom. Qualitative methods were used in analyzing the data, which are the humorous utterances resulted from the maxims flouting found in the first 12 episodes of the series. However, quantitative data is also taken into consideration in the analysis. In the series, a total of 102 occurrences were identified as maxim floutings. The most frequently occurring maxim flouting is of the quality maxim with 56 occurrences (54.90%).The result shows the characters produced verbal humor by flouting the conversational maxims using varied rhetorical strategies. Their most preferred rhetorical strategy is allusion, with 12 occurrences (11.70%) found in the series. It was also discovered that the characters use a variety of rhetorical strategies when they flout the maxims to achieve different communicative goals. The most frequent goal to appear is self-disclosure, with 26 data indicate the speakers flout the maxims to disclose personal information through humor.